1990
DOI: 10.1111/j.1469-7610.1990.tb00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Oppositional Disorder in Children: A Validation Study Comparing Conduct Disorder, Oppositional Disorder and Normal Control Children

Abstract: Subjects with oppositional disorder (OD, N = 21) and conduct disorder (CD, N = 22) were compared with normal controls (NC, N = 20) to determine whether OD is a distinct disorder. OD subjects exhibited high rates of associated attention deficit, emotional and learning disorders. Compared with NC, OD subjects had high rates of problems in social relationships and came from families characterized by marital fights, dysfunction, and paternal psychopathology. Compared with CD, OD was less often characterized by und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Several investigators have found that the DSM-III symptom criterion for OD is overinclusive and not sufficiently stringent Lahey et al, 1990;Schachar & Wachsmuth, 1990). Adoption of a more restrictive criterion is consistent with the thrust of DSM-III-R and DSM-IV reconceptualizations of OD .…”
Section: Diagnostic Subgroupsmentioning
confidence: 78%
“…Several investigators have found that the DSM-III symptom criterion for OD is overinclusive and not sufficiently stringent Lahey et al, 1990;Schachar & Wachsmuth, 1990). Adoption of a more restrictive criterion is consistent with the thrust of DSM-III-R and DSM-IV reconceptualizations of OD .…”
Section: Diagnostic Subgroupsmentioning
confidence: 78%
“…This has the advantage of resembling more closely the definitions adopted in many studies of parent-child interaction and CD, which often involve younger children (Campbell and Ewing, 1990;Dumas, 1986;Forehand and McMahon, 1981;Richman et al, 1982;Webster-Stratton and Hammond, 1988) It also avoids making an unvalidated distinction between the categories of conduct and oppositional disorder, which the current evidence suggests may well represent a continuum of severity of CD rather than distinct categories (Schachar and Wachsmuth, 1990;Werry et al, 1987).…”
Section: Problems Of Definition In Conduct Disordermentioning
confidence: 88%
“…However, this classification system (and its predecessor, DSM-III, 1980) has been subject to much criticism, mainly because of lack of empirical support for a distinction between the above categories and subtypes (Loeber and Lahey, 1989;Loeber and Schmaling, 1985;McMahon, 1987;Quay, 1986a;Schachar and Wachsmuth, 1990;Werry et al, 1987). For example, the list of antisocial acts constituting DSM-III-R criteria for CD includes many serious delinquent acts, which apply mainly to older children, such as stealing, running away overnight, firesetting, housebreaking, and forcing sexual activity on others.…”
Section: Problems Of Definition In Conduct Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this Hurtig et al (2007) reported that adolescents with comorbid CD exhibited more severe symptoms of ADHD than those without CD, and were more likely to come from nonintact families with disaffected mothers. On the other hand the clinical findings of Schachar and Wachsmuth (1990) indicated that forms of ADHD with and without aggression were separate and distinct. Halperin (1991) supported this viewpoint with a description of separate neuropsychological correlates for the two forms.…”
Section: Introductionmentioning
confidence: 99%